The Influence of Auditor Competence, Emotional Intelligence and Auditor Independence on Auditor Performance - Br Purba, Elvira Natalia; Siallagan, Hamonangan; Hutapea, Herti Diana (International Journal on Social Science, Economics and Art, 2025)
The purpose of this study is to determine the auditor's competence, emotional intelligence, and auditor independence on auditor performance. The research method used by researchers in compiling this thesis is a descriptive method. The population in this study were auditors in public accounting offices (kap) in the Medan city area. The results of the partial test can be seen that partially the auditor's competence does not have a positive and significant effect on auditor performance, this is because the provision test in the t test is t count must be greater than t table. The results of the partial test can be partially the auditor's emotional intelligence does not have a positive and significant effect on auditor performance, this is because the provision test in the t test is t count must be greater than t table. And the results of the partial test partially the auditor's independence has a positive and significant effect on auditor performance, this is because the provision test in the t test is t count must be greater than t table